Clinical risk score for postoperative pneumonia following heart valve surgery. Issue 20 (20th October 2021) - Wang, Da-Shuai; Huang, Xiao-Fan; Wang, Hong-Fei; Le, Sheng; Du, Xin-Ling
Abstract: Background: Postoperative pneumonia (POP) is one of the most common infections following heart valve surgery (HVS) and is associated with a significant increase in morbidity, mortality, and health care costs. This study aimed to identify the major risk factors associated with the occurrence of POP following HVS and to derive and validate a clinical risk score. Methods: Adults undergoing open HVS between January 2016 and December 2019 at a single institution were enrolled in this study. Patients were randomly assigned to the derivation and validation sets at 1:1 ratio. A prediction model was developed with multivariable logistic regression analysis in the derivation set. Points were assigned to independent risk factors based on their regression coefficients. Results: POP occurred in 316 of the 3853 patients (8.2%). Multivariable analysis identified ten significant predictors for POP in the derivation set, including older age, smoking history, chronic obstructive pulmonary disease, diabetes mellitus, renal insufficiency, poor cardiac function, heart surgery history, longer cardiopulmonary bypass, blood transfusion, and concomitant coronary and/or aortic surgery. A 22-point risk score based on the multivariable model was then generated, demonstrating good discrimination (C-statistic: 0.81), and calibration (Hosmer-Lemeshow χ 2  = 8.234, P  = 0.312). The prediction rule also showed adequate discriminative power (C-statistic: 0.83) and calibration (Hosmer-Lemeshow χ 2  = 5.606, P  = 0.691) in the validation set. Three risk intervals were defined as low-, medium-, and high-risk groups. Conclusion: We derived and validated a 22-point risk score for POP following HVS, which may be useful in preventive interventions and risk management. Trial Registration: Chictr.org, ChiCTR1900028127; http://www.chictr.org.cn/showproj.aspx?proj=46932